Asset Mapping and Focus Group Usage: An Exploration of the Russian-Ukrainian Population's Need For and Use of Health-Related Community Resources - Jennifer C. Anglin; Tina Kruger Newsham; Matthew Hutchins (The University of Alabama, 2022)
Community resources are an important aspect of preventive medicine and can also provide support to individuals with existing medical conditions. However, resources may not address all population groups within the community equally, and immigrants, who frequently face cultural and language barriers, are often unable to access the full range of healthcare resources available in the community. The purpose of this study was to gain insight on healthcare needs, attitudes, and access of a Ukrainian immigrant population in a large town in northern Indiana. Focus groups were conducted as a first step to creating connections upon which a community-based participatory research project could be built. Findings revealed cultural barriers (lack of understanding of health insurance options or value, belief that similar services were less expensive in the Ukraine) and language issues (lack of translation services or resources written in languages other than English or Spanish) were key barriers to accessing healthcare resources in the community. Concerns about dental care and its expense were also voiced. Future efforts might build on these findings by exploring policies and practices that affect various immigrant groups' access to community healthcare resources. Recommendations for such efforts are also discussed.